Urban form, shrinking cities, and residential carbon emissions: Evidence from Chinese city-regions. (1st March 2020) - Liu, Xingjian; Wang, Mingshu; Qiang, Wei; Wu, Kang; Wang, Xiaomi
Highlights: Shrinking cities tend to be less energy efficient than their growing counterparts. Shrinking cities need to consider the environmental effects of shrinkage. Urban compactness is negatively associated with residential CO2 emissions. Intra-city polycentricity is negatively correlated with gas-related CO2 emissions. Abstract: This paper analyzes the relationship between urban form, shrinking cities, and residential carbon emissions, based on information collected for prefectural-level and above Chinese cities for the years of 2005, 2010, and 2015. After controlling for a number of urban form and socioeconomic variables (e.g., size, compactness, and polycentricity), this paper pays attention to residential carbon emissions in 'shrinking cities', which have experienced population loss and are a recent urban phenomenon in China. Everything else being equal, shrinking cities tend to be associated with less energy efficient than their growing counterparts, suggesting that these cities may not only be 'battling' with shrinking populations and economies but also need to consider the environmental issues.